Development of refrigeration and heat pump systems - Pearson, Andy (Frontiers in Thermal Engineering, 2022)
Despite continual development over more than two centuries there is still great scope for significant development in the realms of mechanical cooling and heating. This paper reviews the nature of the historical development and identifies key motivations for technical development. It seeks to highlight where there is greatest need for future development in this ubiquitous technology.